1998
DOI: 10.1073/pnas.95.19.11493
|View full text |Cite
|
Sign up to set email alerts
|

Both here and there: Simultaneous expression of autonomous spatial memories in rats

Abstract: Foraging rats learned to avoid footshock that was present in a part of a circular arena that was either stable or rotating slowly in a lighted room. The rotation dissociated spatial information in the separate reference frames of the room and arena. After learning to avoid the shocked region in either condition, in the absence of shock, memory for this place was expressed by simultaneous avoidance of an area defined in the reference frame of the room as well as of an area defined in the reference frame of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 18 publications
3
68
0
Order By: Relevance
“…Previous functional inactivation of the dorsal hippocampus blocked both the acquisition of spatial memories and the retrieval of long‐term spatial avoidance memories on the APA (Fenton et al. 1998; Cimadevilla et al. 2000; Kubik and Fenton 2005; Wesierska et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous functional inactivation of the dorsal hippocampus blocked both the acquisition of spatial memories and the retrieval of long‐term spatial avoidance memories on the APA (Fenton et al. 1998; Cimadevilla et al. 2000; Kubik and Fenton 2005; Wesierska et al.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse was trained to avoid a 60° shock zone, which could be defined within a region of the room identified by multiple visual cues (Fenton et al. 1998; Wesierska et al. 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The place avoidance system (Bio-Signal Group) was adapted from that used in previous studies (Bureš et al, 1997;Fenton et al, 1998;Cimadevilla et al, 2000Cimadevilla et al, , 2001. The arena was a uniform metal disk, 82 cm in diameter, with a 5-cm-high wall.…”
Section: Room؉ Place Avoidance Apparatusmentioning
confidence: 99%
“…1C). Note, however, that there is an additional challenge in RoomϩArenaϪ avoidance and even more so in the RoomϩArenaϩ (Fenton et al, 1998) avoidance task in which the rat must avoid both a stationary and a rotating place, because entering either region is punished by footshock. The rat must segregate stationary room and rotating arena stimuli and selectively associate shock with the appropriate stimulus subset.…”
Section: Segregation and Representation-distinct Hippocampal Functionsmentioning
confidence: 99%
“…Recent research (17,18,21) demonstrated that rats learn to efficiently avoid an unmarked place on a dark rotating arena. Navigation in the arena frame could be supported by substratal idiothesis and by substratal cues, but not by extramaze cues and inertial idiothesis.…”
Section: Methodsmentioning
confidence: 99%